ChemInform Abstract: Cerium Valence Change in the Solid Solutions Ce(Rh1‐χRuχ)Sn. Issue 48 (26th November 2013) - Niehaus, Oliver; Abdala, Paula M.; Riecken, Jan F.; Winter, Florian; Chevalier, Bernard; Poettgen, Rainer
Abstract A series of 15 samples in the system Ce(Rh1‐xRux)Sn (0 ≤ x ≤ 1) is prepared by arc melting of stoichiometric mixtures of the elements.